Creating Tourism Camp for Youth - Sainaratchai, Krittika; Kieanwatana, Komsit (Journal of Cultural Approach, 2016)
The tourism camp is deemed as one of outdoor recreation activities apposite for youth. The activity helps in broadening the youth’s knowledge horizon as well as enhancing their experiences through tourism camp field trips which entices them not only to become exposed to more knowledge and experiences pertaining to natural resources, natural environment, arts and cultures, and traditions, but also to learn how to adapt themselves in order to behave and treat other people at the same time. Strengthening their sense of responsibility, unity, leadership and being a good follower through various activities can help to develop.